Human Resource Audit Practices in Regional State-Owned Banking: Praktik Audit Sumber Daya Manusia di Bank Milik Negara di Tingkat Regional - Dian Rif’atul Hidayah; Dina Dwi Oktavia Rini (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Human resource management is a strategic element in achieving organizational performance in the banking sector. Specific Background Bank Tabungan Negara implements human resource audits as part of internal control to ensure compliance with policies and alignment with business strategy. Knowledge Gap Limited empirical studies evaluate human resource audit implementation focusing on employee placement at the regional level. Aims This study aims to evaluate the implementation of human resource audits and examine employee performance after audit application at Bank Tabungan Negara Regional Office of East Java, Bali, and Nusa Tenggara. Results Findings show that human resource audits are conducted according to standard operating procedures and good corporate governance principles, with systematic stages and follow-up actions. Employee performance demonstrates improvement based on key performance indicators and organizational values. Novelty This study provides contextual evidence of human resource audit practices within a regional state-owned bank environment. Implications The findings support the use of human resource audits as an internal evaluation mechanism to strengthen human capital management and organizational performance. Highlights: Audit procedures align with internal policies and governance principles Employee placement evaluation improves workforce distribution Performance indicators show measurable improvement after audits Keywords: Human Resource Audit, Employee Performance, Internal Control, State-Owned Bank, Human Capital